O significado do estágio de fisioterapia numa instituição de longa permanência para idosos - Bispo, Nuno de Noronha da Costa (2008)
The São Vicente de Paulo Nursing Home, in Londrina, was created to minimize the effects of the social problems, commonly found in large cities, which, at that time, were booming due to the wealth generated by the coffee culture. As time went by, the institution continued to fulfill the demands of the society regarding its care for the city s elderly people, and developed a Supervised Practicum in Physical Therapy, based on the Movement Continuum Theory . The general objective of this qualitative research was to verify the significance of the Physical Therapy Practicum to an institution of long permanence for elderly people. Data were collected through a non-structured interview carried out with 21 elderly people, and analyzed according to hermeneutics - dialectic method. Results showed that the Practicum has plural senses by the number of significances assigned to it. In the final considerations of this study, the importance of researching into actions of this nature to build a community of the future is emphasized